Paham Nasionalisme dan Pergerakan Kebangsaan di Indonesia dari Tahun 1900-1942 - Iramdhan Iramdhan (Universitas Indraprasta PGRI, 2017)
ABSTRACTPenelitian aims to understand or further understand the role of nationalist understanding of the nationalist movement in Indonesia. The method used in this research is a literature study method to conduct research some important documents, read and examine the books and other resources related to the title. Heuristics, with traces of book collecting relics of the past, as well as make comparisons avatar opinion of some writers who have some differences. Historically, many methods used in historical research merekonstraksikan past attempts to systematically and objectively by collecting and evaluating and systematize robust conclusions that are connected with the facts. The results of this study indicate that in general national movement in opposing and fighting the invaders are repleksi resistance as a result of repression committed by the invaders. Growing and growing nationalist movement carried out by the Indonesian figures are also influenced by the ideology of new growth in mainland Europe in its time was the idealism formation of dissatisfaction with layers of European society in the joints of life, growth, and development of Understand-understood new such as nationalism, liberalism, socialism and democracy that spread across the world make basic materials rose and the growth of the Indonesian National movement. In addition to the influence of Understand-understood new Indonesian national movement also influenced by the presence of the nationalist movement that occurred in mainland Asia and Africa, Imperialism western nations lead the nations of the Asia-Africa losing political independence, on the other nations of Asia and Africa are also experiencing suffering in social-economic and cultural. Asian-African nationalism not only wants to pursue national independence but also has other properties that have some aspect of Indonesian National opening. Pergerakan is a reflection of a sense sebuh oppressed because of colonization that happened, the development of the Indonesian National Movement is a process of resistance undertaken by the Indonesian people because of the existence of the factors driving the arrival of domestic and external factors, as well as their understanding of the formation of new ideologies and national movements grew in Asia and Africa. Keywords: Understand Nationalism and National Movement in IndonesiaABSTRAKPenelitian ini betujuan untuk memahami atau memahami lebih jauh peranan paham nasionalime terhadap pergerakan kebangsaan di Indonesia. Metode yang digunakan dalam penelitian ini adalah metode studi kepustakaan dengan mengadakan penelitian beberapa dokumen penting, membaca serta meneliti buku-buku dan sumber lainnya yang berkaitan dengan judul. Heuristik, dengan menghimpun jejak buku peninggalan masa lampau, serta mengadakan perbandingan anatar pendapat beberapa penulis yang memiliki beberapa perbedaan. Historis, metode yang banyak digunakan dalam penelitian sejarah yang mencoba untuk merekonstraksikan masa lampau secara sistematis dan obyektif dengan cara mengumpulkan dan mengevaluasi serta mensistematiskan kesimpulan yang kuat yang dihubungkan dengan fakta. Hasil Penelitian ini menunjukkan bahwa pada umumnya pergerakan nasional dalam menentang dan melawan penjajah adalah repleksi perlawanan sebagai akibat penindasan yang dilakukan oleh penjajah. Tumbuh dan berkembangnya Pergerakan nasional yang dilaksanakan oleh para tokoh Indonesia juga dipengaruhi oleh paham-paham baru yang berkembang didaratan Eropa yang pada zamannya merupakan idealisme pembentukan dari rasa ketidakpuasan lapisan masyarakat Eropa pada sendi-sendi kehidupan, Tumbuh dan berkembangnya Paham-paham baru seperti nasionalisme, liberalisme, sosialisme dan demokrasi yang menyebar ke seluruh dunia menjadikan bahan dasar bangkit dan tumbuhnya Pergerakan Nasional Indonesia. Selain adanya pengaruh Paham-paham baru, pergerakan nasional Indonesia juga dipengaruhi oleh adanya pergerakan kebangsaan yang terjadi di daratan Asia dan Afrika, Imperialisme bangsa barat menyebabkan bangsa-bangsa di Asia-Afrika kehilangan kemerdekaan politik, selain itu bangsa-bangsa Asia-Afrika juga mengalami penderitaan dibidang sosial-ekonomi dan kebudayaan. Nasionalisme bangsa Asia-Afrika bukan hanya mau mengejar kemerdekaan nasional melainkan juga mempunyai sifat-sifat lain sehingga memiliki beberapa aspek penting.Pergerakan Nasional Indonesia merupakan sebuh refleksi dari rasa tertindas karena penjajahan yang dialaminya, perkembangan Pergerakan Nasional Indonesia merupakan proses perlawanan yang dilakukan oleh bangsa Indonesia karena adanya dari faktor-faktor pendorong yang datangnya dari dalam negeri maupun faktor dari luar serta adanya pemahaman dari sekian pembentukan paham-paham baru serta pergerakan nasional yang tumbuh di Asia dan Afrika.Kata kunci: Paham Nasionalisme dan Pergerakan Kebangsaan di Indonesia